The internal rate of return (IRR): projections, benchmarks and pitfalls. Issue 6 (5th September 2016) - Patrick, Michael; French, Nick
Abstract : Purpose: The purpose of this paper is to discuss the use of the internal rate of return (IRR) as a principal measure of performance of investments and to highlight some of the weaknesses of the IRR in evaluating investments in this way. Design/methodology/approach: This Education Briefing is an overview of the limitations of the IRR in making capital budgeting decisions. It is illustrated with a number of counter-intuitive examples. Findings: The advantage of the IRR is that it is, on the surface, a wonderfully simple benchmark. One figure that tells a story. But, the disadvantage is that if used in isolation the IRR can give misleading results when used to assess investment proposals. Practical implications: The IRR should be used in conjunction with other analyses to appraise projects, so that the user can determine its veracity in the context of other benchmarks. This context is particularly important when assessing investments with unusual cash flows. Originality/value: This is a review of existing models.